(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study was about the existence of CALP (academic words) in report text for second grade senior high school. The aim of this study was to find out 1) the percentage and 2) the frequency of academic words (CALP words) contained in report text used for second grade senior high school. Six report texts from three different publishers were chosen through purposive sampling. The analysis was based on the Academic Word List (AWL) which comprises of 10 level of frequency, from the highest (level 1) to the lowest (level 10). It was found that there were 33 academic words in the six report texts, and 12 of them or 36.37% belong to level 1. It implies that most academic words contained in the texts belong to the highest frequency level. Based on the result, it is recommended for teachers to concern more on material selection to fulfill students need in academic words.